2021
DOI: 10.3389/fpls.2021.670803
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Response of Tropical Fruits to Hypoxia/Anoxia

Abstract: Aerobic respiration and oxygen consumption are indicators of routine metabolic rate, and dissolved oxygen in plant tissues is one of the most important environmental factors affecting their survival. The reduction of available O2 leads to hypoxia which causes a limitation of the oxidative phosphorylation; when O2 is absent, tissues generate ATP by activating the fermentative glycolysis to sustain glycolysis in the absence of mitochondrial respiration, which results in the production of lactate. Overall, hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…Despite a declined SSC value being observed in pulps that had been stored at RT for 72 h ( Figure 1 C), the contents of α-glucose, β-glucose, fructose, and sucrose were statistically stable within 72 h at the two set storage temperatures ( Figure 3 ). On the one hand, the soaring lactate indicated extremely active anaerobic glycolysis and glucose dissipation in pulp cells [ 32 ]. On the other hand, firmness loss might upregulate the concentration of sugars to a greater or lesser degree.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a declined SSC value being observed in pulps that had been stored at RT for 72 h ( Figure 1 C), the contents of α-glucose, β-glucose, fructose, and sucrose were statistically stable within 72 h at the two set storage temperatures ( Figure 3 ). On the one hand, the soaring lactate indicated extremely active anaerobic glycolysis and glucose dissipation in pulp cells [ 32 ]. On the other hand, firmness loss might upregulate the concentration of sugars to a greater or lesser degree.…”
Section: Resultsmentioning
confidence: 99%
“…Intense transcriptional reprogramming is observed in fruit under low oxygen pressures 13 . Hypoxia also affects directly ethylene biosynthesis and tissue responsiveness to the hormone 13,14 . The metabolic pathways most significantly affected by hypoxia are sucrose catabolism, anaerobic fermentation, and reactive oxygen species regulation, and current evidence indicates that low oxygen levels affect differently ripening and senescence metabolic process 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…The responses to hypoxia in fruit tissues include a reduction in cellular respiration and ethanol biosynthesis, followed by the induction of anaerobic respiration, affecting the transport of metabolites and several energy‐associated pathways, including glycolysis, the cycle of tricarboxylic acids (TCA) and the metabolism of amino acids 13 . The reduction in cellular levels of O 2 also affect ethylene production and tissue sensitivity negatively 13,14 . As a consequence of the modifications in fruit physiological and metabolic processes, hypoxia delays ripening and senescence of fruit 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly recognised that fresh-cut fruits have higher respiratory rate than the corresponding intact fruits due to the physical injury from minimal process (Allong et al, 2001). Therefore, the short-term anoxia treatment could maintain total sugars content through the control of increased respiration rate (Benkeblia, 2021). Lara et al (2011) reported that the contents of sucrose, fructose and glucose in short-term anoxia-treated peaches remained unchanged when compared to untreated fruits.…”
Section: Total Sugars Contentmentioning
confidence: 99%